1997
DOI: 10.1002/(sici)1097-4547(19970315)47:6<573::aid-jnr2>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Binding of microtubules to transitional elements in oligodendrocytes of the myelin mutanttaiep rat

Abstract: The presence of microtubules physically bound to smooth endoplasmic reticulum profiles of oligodendrocytes constitutes the most conspicuous feature observed in the myelin mutant taiep rat. The endoplasmic reticulum membranes associated with microtubules were morphologically characterized as transitional elements that constitute the intermediate compartment according to their topographic location close to the cis‐Golgi apparatus. The development of this surprising microtubular defect appears to be associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The mutation in the taiep rats that causes the microtubule accumulation in the oligodendrocyte and the consequent hypomyelination is still unknown [ 1 , 2 , 50 ]. Our results strongly suggest that the deficiency of the remyelination-stimulating factors such as CXCL1 and CXCR4 contributes to the failure in the process of remyelination in a microenvironment of chronic inflammation in the taiep rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutation in the taiep rats that causes the microtubule accumulation in the oligodendrocyte and the consequent hypomyelination is still unknown [ 1 , 2 , 50 ]. Our results strongly suggest that the deficiency of the remyelination-stimulating factors such as CXCL1 and CXCR4 contributes to the failure in the process of remyelination in a microenvironment of chronic inflammation in the taiep rats.…”
Section: Discussionmentioning
confidence: 99%
“…The taiep rats exhibit hypomyelination and suffer progressive demyelination resulting in a highly hypomyelinated central nervous system (CNS) as they reach adulthood [ 1 , 2 ]. This demyelinating process has been associated with nitrosative stress in vivo and in vitro [ 3 , 4 ], glial-microglial activation and lymphocyte migration [ 4 ], and an increase in lipoperoxidation, caspase-3 activation, and cell death in vivo [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Holmgren et al 1989) characterized by abnormal myelination (dysmyelination) and subsequent demyelination of the CNS (Duncan et ai. 1992;Couve et al 1997), due to a microtubular defect in oligodendrocytes (OLs). The optic nerve, myelinated by OLs, provides a suitable model of the CNS tract.…”
Section: Cb Crmentioning
confidence: 99%
“…It was obtained at the Institute of Physiology of the Beneme ´rita Universidad Auto ´noma de Puebla, Me ´xico, as a spontaneous recessive tubulin mutation during the inbreeding process to obtain a subline of Sprague-Dawley with highyawning frequency [3,4]. The genetic change causes an initial hypomyelination followed by a progressive demyelination exclusively in the central nervous system (CNS) with a somatic recessive inheritance [3,5,6]. Recently, our research group demonstrated that taiep rats have a point mutation in Tubb4a gen and its corresponding protein TUBB4A (OMIM 602662), with pathological characteristics similar to the human leukodystrophy hypomyelination with atrophy of the basal ganglia and cerebellum (H-ABC); [7,8].…”
Section: Introductionmentioning
confidence: 99%